Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12934-022-01801-9
|View full text |Cite
|
Sign up to set email alerts
|

Active secretion of a thermostable transglutaminase variant in Escherichia coli

Abstract: Background Streptomyces mobaraenesis transglutaminase (smTG) is widely used to generate protein crosslinking or attachment of small molecules. However, the low thermostability is a main obstacle for smTG application. In addition, it is still hard to achieve the secretory expression of active smTG in E. coli, which benefits the enzyme evolution. In this study, a combined strategy was conducted to improve the thermostability and secretory expression of active smTG in E. coli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We previously reported that cultivation at 20 °C and using a thioredoxin (TrxA) fusion tag contributed to high mTG expression levels. , The contributions of constitutive promoters for promoting soluble enzyme expression was evaluated by cultivation at 20 and 30 °C. mTG was recombinantly expressed in zymogen form carrying TrxA and the pro-region from Streptomyces hygroscopicus proH.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that cultivation at 20 °C and using a thioredoxin (TrxA) fusion tag contributed to high mTG expression levels. , The contributions of constitutive promoters for promoting soluble enzyme expression was evaluated by cultivation at 20 and 30 °C. mTG was recombinantly expressed in zymogen form carrying TrxA and the pro-region from Streptomyces hygroscopicus proH.…”
Section: Resultsmentioning
confidence: 99%
“…mTG was recombinantly expressed in zymogen form carrying TrxA and the pro-region from Streptomyces hygroscopicus proH. The bands at 48–62 kDa corresponding to the molecular weight of mTG (56.5 kDa) , displayed minor differences using different promoters of both soluble and insoluble fractions, which may be a result of previous expression optimization (Figure S5). Following cultivation at 20 °C, mTG induced by the N19 and T7 promoters displayed the highest intracellular activity, which reached 12 and 9.6 U/mL, respectively (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations